Distinct miRNA Gene Expression Profiles Among the Nodule Tissues of Lung Sarcoidosis, Tuberculous Lymphadenitis and Normal Healthy Control Individuals - Zhao, Ya-bin; Li, Wei; Zhang, Qin; Yin, Yan; Yang, Chuan-jia; Xu, Wen-xiang; Kang, Jian; Qi, Rui-qun; Hou, Gang (Frontiers in Medicine, 2020)
Background: Sarcoidosis and tuberculosis share similarities in clinical manifestations and histopathological features. We aimed to identify the microRNA (miRNA) profiles of the lymph nodes of individuals with sarcoidosis and of those with tuberculous lymphadenitis to investigate the value of miRNAs in the differential diagnosis of sarcoidosis and tuberculous lymphadenitis. Methods: The miRNA profiles of the lymph nodes of individuals with sarcoidosis, those with tuberculous lymphadenitis (TBLN) and controls were detected by miRNA microarray analysis in the age- and sex-matched development group of the controls (n=3), patients with TBLN (n=3) and patients with sarcoidosis (n=3), and the results were validated by quantitative real-time polymerase chain reaction in the validation group of the controls (n=30), TBLN (n=30) and patients with sarcoidosis (n=31). The relationship between miRNA expression and the clinical parameters of sarcoidosis was analyzed. Results: miR-145, miR-185, miR-301, miR-425-5P, miR-449b and miR-885-5P were differentially expressed between individuals with sarcoidosis and controls (P<0.0001, P<0.0001, P=0.0008, P=0.0002, P=0.0018 and P<0.0001, respectively), and the same six miRNAs were differentially expressed between individuals with tuberculous lymphadenitis and controls (P=0.0002, P=0.0004, P=0.0238, P=0.0006, P=0.0149 and P=0.0045, respectively). miR-185 was differentially expressed between individuals with tuberculous lymphadenitis and those with sarcoidosis (P=0.0101). The area under the receiver operating characteristic curve calculated for miR-185 was 0.6860, and the sensitivity and specificity of miR-185 for the differential diagnosis of sarcoidosis from TBLN were 61% and 80%, respectively. The levels of miR-145, miR-301, miR-425-5P and miR-885-5P were positively correlated with CD4+/CD8+ T lymphocytes in bronchoalveolar lavage fluid. Conclusions: miRNAs in lymph nodes show similar expression patterns between individuals with sarcoidosis and those with tuberculous lymphadenitis, which were experimentally selected. miR-185 in the lymph nodes can be used as an auxiliary marker for the differential diagnosis of sarcoidosis and tuberculous lymphadenitis.